Use of plant bioindicators to identify residues of herbicides in the soil (Research, Society and Development, 2020)
This work was based on a bibliographic survey. Scientific papers (articles, theses and dissertations) published between 1988 and 2020 were consulted, which contained data on the use of the bioassay technique. The bioassay is one used to determine the existence of herbicide residues in the soil. In its realization, species sensitive to the herbicide (bioindicators) are used. To be considered a bioindicator, the plant species must have sensitivity to the herbicide studied, presenting phytointoxication and reduction in physical or physiological characteristics. In addition, the sensitivity should increase according to the increase of residues in the soil. Due to the mechanism of action and sorption of the herbicide, each compound has ideal bioindicator species. The present study aimed to verify in the literature bioindicator species for residual herbicides, depending on the texture of the soil and the analyzed variable. It brings a generalist approach to species whose sensitivity to herbicides has been experimentally proven, allowing consultation of the ideal bioindicator for each compound. It was found in the literature that the species Cucumis sativus and Sorghum bicolor are the most used as bioindicators and the herbicides atrazine and sulfentrazone the most reported.